Impact of the COVID-19 Pandemic on Burnout Syndrome for Nurses - Klišys, Edgaras; Mikaliūkštienė, Aldona; Fatkulina, Natalja (Slauga. Mokslas ir praktika, 2022)
Burnout syndrome has been around for decades and affects many professions. Burnout is defined as the exhaustion of physical or emotional strength or motivation, usually as a result of prolonged stress or frustration. Researchers agree that burnout is a process, but divide it into several distinct stages. Burnout syndrome is not only caused by the personal characteristics of individuals working in healthcare settings, but also by a variety of environmental factors that affect each individual in one way or another. In the wake of the COVID-19 pandemic, these factors have been compounded by additional stressors, which have influenced the prevalence of burnout in nurses, and recent studies have shown an increase in the number of nurses suffering from burnout. This has made the prevention and management of burnout even more relevant in today’s context. The aim of this paper is to review and present the recent literature on burnout syndrome experienced by nurses in the COVID-19 setting. Methods - Systematic search of PubMed and Google Scholar databases for articles. The results showed that the COVID-19 pandemic has a significant impact on the occurrence of burnout syndrome in nurses.